A lightweight, lithium-philic composite current collector and a method for preparing the same

Copper nanoparticles were prepared and modified by wet chemistry, combined with low-temperature sintering technology, and lightweight, lithium-philic composite fluids were prepared, solving the problem of complex and high cost of composite copper foil preparation process in the existing technology, and realizing lithium ion Improvement of battery energy density and development of industrialization potential.

CN116093338BActive Publication Date: 2025-02-18XIAMEN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310169817.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-27
Publication Date
2025-02-18
Estimated Expiration
2043-02-27

AI Technical Summary

Technical Problem

In the process of increasing the energy density of lithium-ion batteries, the preparation process of composite copper foil is complex and costly, and the thickness of the copper foil on both sides is difficult to further reduce, which limits the increase of battery energy density.

Method used

Copper nanoparticles were prepared by wet chemistry, and lightweight, lithium-philic composite fluid was prepared through formate modification and low-temperature sintering technology, combined with functional coating slurry design.

Benefits of technology

The lightweight and lithium-philicity of the current collector are achieved, which reduces the overall weight of the battery, increases the energy density, and reduces the preparation cost, and has industrialization potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116093338B_ABST
    Figure CN116093338B_ABST
Patent Text Reader

Abstract

The present invention relates to a lightweight, lithium-philic composite current collector and a preparation method thereof, wherein the steps include: using copper nitrate and a reducing agent to drip into a solution containing a surfactant to synthesize copper nanoparticles of uniform size; removing impurities in the copper nanoparticle dispersion by centrifugal washing; dispersing the copper particles in a modification solution and modifying the formate protective layer on the surface by heat treatment; centrifuging the modified antioxidant, lithium-philic copper particles, adding a copper amine ligand to prepare a copper slurry, and coating it on a polymer substrate material; and then sintering at low temperature in a nitrogen atmosphere to obtain a composite current collector. This composite current collector is lightweight and can improve the weight density of the battery; the use of lithium-philic copper particles can effectively regulate the deposition behavior of lithium metal and inhibit the generation of lithium dendrites; it is expected to be used in the construction of high-energy-density lithium metal batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of lithium ion batteries and lithium metal batteries, and in particular to the preparation and application of a lightweight lithium-philic composite current collector. Background Art

[0002] Lithium-ion batteries are the most widely used and most mature secondary battery system, mainly composed of positive electrode materials, negative electrode materials, separators, current collectors, and electrolytes. With the increasing development of social economy, people's demand for battery energy density is getting higher and higher. Therefore, it is urgent to find ways to increase battery energy density. There are two main ways to increase battery energy density. One is to reduce the proportion of inactive substances, and the other is to find other active material systems that can increase energy density.

[0003] The current collector is an indispensable component for connecting lithium-ion batteries and external circuits. As an inactive material in lithium-ion batteries, it accounts for 15% of the battery. Therefore, reducing the thickness of the current collector can reduce the overall weight of the lithium-ion battery, thereby improving the battery energy density. In recent years, in order to improve the battery energy density, the thickness of the current collector has been continuously reduced, and the thickness of the copper current collector has been reduced from the initial 20μm to the current 4-6μm. However, blindly reducing the thickness of the current collector will have a great impact on the mechanical properties, conductivity, and heat transfer properties of the current collector. Therefore, it is imperative to find other ways to reduce the weight of the current collector. In order to effectively reduce the weight of the current collector while maintaining good mechanical properties, the concept of composite current collectors has attracted attention in recent years. For example, Cui Yi et al. deposited a 500nm thick copper nanoparticle layer on both sides of PI (polyimide) by magnetron sputtering to replace ordinary copper foil as a current collector (Nature Energy 2020, 5, 299–308). At the same time, they added flame retardant materials in the middle of PI to improve the safety performance of the battery. Patent CN112615010A reports a method for preparing a lightweight current collector by spraying a metal layer on the surface of a polymer using a vacuum magnetron sputtering method. Compared with commercial metal foil current collectors, the prepared battery can achieve a specific energy increase of 16-26%. Patent CN114161787A reports a composite copper foil technology, that is, a layer of copper foil is pressed on both sides of the hot-melt insulating resin by an extrusion molding method, and then the semi-finished copper foil is reduced according to demand to obtain a composite copper foil with thinner thickness on both sides. Compared with ordinary copper foil, this technology has improved the surface density and material thickness to a certain extent. From the above research and the technology disclosed in the existing patents, the preparation of composite copper foil still has great limitations, mainly focusing on physical methods. The use of magnetron sputtering and vacuum coating methods to prepare copper films on the surface is relatively complex and costly, which limits its industrial application to a certain extent. Although the process of using extrusion molding is relatively simple, it is difficult to further reduce the thickness of the copper foil on both sides, and the improvement of battery energy density is limited. Therefore, it is of great significance to develop new processes for preparing lightweight composite current collectors based on wet chemical methods and traditional coating processes.

[0004] In addition, lithium metal has an ultra-high theoretical specific capacity and the lowest electrochemical reduction potential, making it one of the most promising next-generation negative electrode materials today. Using lithium metal anodes instead of traditional graphite can significantly improve the energy density of batteries. However, due to the high reactivity of lithium metal, there are a series of problems in its application, such as lithium dendrites, volume expansion, unstable SEI film, etc. Using current collectors to regulate the deposition behavior of metallic lithium and then stabilize the lithium metal anode is considered to be an effective way to improve the performance of lithium metal batteries. Therefore, composite current collectors with lithium-philic properties that can improve lithium deposition efficiency have good application potential in the next generation of high-performance lithium metal batteries.

[0005] However, copper nanoparticles prepared by wet chemical methods have poor oxidation resistance and are difficult to store and use for a long time. In general, copper materials have poor affinity for lithium. Metallic lithium easily forms dendrites when deposited on commercial copper foil, so the deposition efficiency is low. It is challenging to use wet chemical methods that are easy to prepare on a large scale to construct lightweight, lithium-philic composite current collectors that can be stably stored and used. Summary of the invention

[0006] Therefore, we hope to develop an effective method for preparing anti-oxidation and lithium-philic wet chemical copper nanoparticles to develop a new manufacturing strategy for composite current collectors. By combining functional coating slurry design with low-temperature sintering technology, we can effectively improve the stability of the composite current collector and ultimately obtain a lightweight, lithium-philic composite current collector.

[0007] In recent years, the development direction of batteries is mainly to increase the energy density of batteries. Therefore, it is very important to reduce the weight of the current collector. Therefore, one of the purposes of the present invention is to use copper nanoparticles in a wet chemical method to reduce the weight of the current collector. The second purpose of the present invention is to improve the lithium affinity of the current collector and prepare a composite current collector that is both lightweight and lithium-philic. The third purpose of the present invention is to reduce the preparation cost so that the composite current collector in the present invention has industrialization potential.

[0008] In order to achieve at least one of the above purposes, the technical solution of the present invention is:

[0009] A lightweight, lithium-philic composite current collector comprises a plastic substrate layer and a copper particle layer attached to the plastic surface, wherein the plastic substrate layer has a thickness range of 4-12 μm and can withstand sintering at 200°C-270°C for 10-60 min; the surface of the copper particles is modified with formate and sintered at 200°C-270°C for 10-60 min. The copper particles are prepared by a wet chemical method and applied to the surface of the substrate material by a scraping method.

[0010] Preferably, the copper nanoparticle layer has a thickness ranging from about 500 nm to about 1.5 μm.

[0011] Preferably, the thickness of the plastic base layer is in the range of 4-8 μm. More preferably, the thickness of the plastic base layer is in the range of 4-6 μm.

[0012] In the present invention, the plastic base layer is at least one of PPS (polyphenylene sulfide), PAR (polyarylate), PI (polyimide), PEEK (polyetheretherketone resin), POB (polyphenylene ester), and PF (phenolic resin).

[0013] Plastics are divided into low heat resistant plastics, medium heat resistant plastics and high heat resistant plastics.

[0014] Low heat-resistant plastics: a type of resin with a heat deformation temperature of less than 100°C. Specific varieties include: PE, PS, PVC, PET, PBT, ABS, and PMMA. Medium heat-resistant plastics: a type of resin with a heat deformation temperature between 100-200°C. Specific varieties include: PP, PVF, PVDC, PSF, PPO, and PC.

[0015] High heat-resistant plastics: The heat deformation temperature of polyphenylene sulfide (PPS) can reach 240°C, the heat deformation temperature of chlorinated polyether can reach 210°C, the heat deformation temperature of polyarylate (PAR) can reach 280°C, the heat deformation temperature of polyetheretherketone resin (PEEK) can reach 230°C, the heat deformation temperature of polyphenylene ester (POB) can reach 260-300°C, the heat deformation temperature of fusible polyimide (PI) is 270-280°C, the heat deformation temperature of aminoplast is 240°C, the heat deformation temperature of (phenolic resin) PF can reach 200°C, and the heat deformation temperature of tetrafluoroethylene (F4) is 260°C.

[0016] In the present invention, low heat-resistant plastics and medium heat-resistant plastics having a heat deformation temperature lower than 200° C. do not meet the requirements.

[0017] Another technical solution of the present invention is:

[0018] A method for preparing a lightweight, lithium-philic composite current collector comprises the following steps:

[0019] 1) Synthesizing copper nanoparticles;

[0020] 2) dispersing copper nanoparticles in a modification solution and modifying the surface with formate by heating;

[0021] 3) coating the modified copper particles on a plastic substrate material to obtain a composite current collector;

[0022] 4) Sinter the composite current collector at 200° C.-270° C. for 20-80 min.

[0023] Furthermore, in step 1), copper nitrate and hydrazine hydrate solution are simultaneously added dropwise to a PVP (polyvinyl pyrrolidone K30) aqueous solution to react and obtain a copper nanoparticle dispersion.

[0024] Furthermore, in step 1), the concentration of copper nitrate is 0.5-3 mol / L, the concentration of hydrazine hydrate is 3-7 mol / L, and the mass concentration of PVP is 0.01-0.10 g / mL; the volume ratio of copper nitrate solution: hydrazine hydrate solution: PVP aqueous solution is 30-50:30-50:120-180.

[0025] Furthermore, the copper nitrate and hydrazine hydrate are added dropwise simultaneously, with a dropping rate of 5-10 ml / min and a temperature of 75-95° C. during the dropping.

[0026] Furthermore, the modification solution in step 2) is obtained by dissolving sodium formate and copper formate in ethylene glycol. The concentration of sodium formate is 0.05-0.5 mol / L, and the concentration of copper formate is 0.00005-0.0005 mol / L.

[0027] Furthermore, the mass concentration of the copper particles in the modification solution is 0.01-0.5 g / mL.

[0028] Furthermore, during the modification process, nitrogen or inert gas is passed and the temperature is maintained at 120-180° C. for 0.5-2 h.

[0029] Furthermore, in step 3), the modified copper particles are first configured into copper paste and then coated, the solvent used in the copper paste is isopropanol, and the mass fraction of the copper particles is 30-40wt%.

[0030] In the technical solution of the present invention, the size and uniformity of the copper nanoparticles can be controlled by controlling the concentration and drop rate of copper nitrate and hydrazine hydrate. In order to prepare copper particles with uniform size and small particles, the preferred drop rate is 8ml / min. The preferred copper nitrate concentration is 1.25mol / L, and the hydrazine hydrate concentration is 5mol / L. The modification solution selected in the modification step is obtained by dissolving sodium formate and copper formate in ethylene glycol. The modification is used to modify the surface of the copper particles with formate, thereby improving their antioxidant properties and lithium affinity.

[0031] In step 1), preferably, when the dropwise addition starts, the temperature of the PVP aqueous solution is selected to be 85° C. The amount of copper nitrate and hydrazine hydrate is 40 ml, the mass of PVP is 5 g, and the amount of solvent water is 150 ml.

[0032] Before step 2), the copper nanoparticles are preferably washed by centrifugation. Since the synthesized copper particles are relatively small, preferably, the speed of centrifugation is 11000 r / min and the time is 4 min.

[0033] In step 2), the formate in the modification solution is obtained by sodium formate and copper formate. Preferably, the concentration of sodium formate is 0.2 mol / L, and the concentration of copper formate is 0.0002 mol / L. Preferably, the temperature is maintained at 160° C. during modification. After one hour of reaction under nitrogen, the modification is completed, and the solution temperature is lowered to room temperature by ice bath.

[0034] In step 3), 5-15% of copper amine ligand is also added to the copper slurry.

[0035] The copper amine ligand is formed by the complexation of copper formate and AMP (isobutanolamine). The molar ratio of copper formate to AMP is 1:1-3. The preparation method can be achieved by stirring and mixing and reacting at 30-70°C for 1-3h to fully react.

[0036] In step 2), the copper particles are dried by nitrogen purge. Preferably, the concentration of the copper particle slurry after modification is 34 wt %. The proportion of the copper amine ligand added is 10 wt %.

[0037] In step 3), preferably, the coating is performed by drawing the film using a scraper with a gap of 100 μm to obtain a copper film with a thickness of about 1 μm.

[0038] In step 4), preferably, the sintering temperature is 250° C. and the sintering time is 20 min. A conductive composite copper current collector is obtained.

[0039] The advantages of the present invention are as follows:

[0040] 1. A lightweight, lithium-philic composite current collector of the present invention comprises a plastic base layer and a copper particle layer attached to the plastic surface, wherein the thickness of the plastic base layer is in the range of 4-12 μm. Since the density of plastic is much lower than that of copper, the weight of the current collector can be greatly reduced.

[0041] 2. The copper nanoparticles have been modified with formate, which greatly improves their antioxidant properties and lithium affinity.

[0042] 3. The copper particles are sintered at 200℃-270℃ for 10-60min to improve conductivity.

[0043] 4. Compared with copper foil, copper nanoparticles have a larger surface area and are more conducive to binding lithium.

[0044] 5. The method of the present invention requires extremely simple equipment and low production cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 Schematic diagram of the structure of the composite current collector of the present invention

[0046] Figure 2 This is a planar SEM image of the synthetic copper particles in Example 1.

[0047] Figure 3 This is a cross-sectional SEM image of the copper particles coated on the substrate in Example 1

[0048] Figure 4 The SEM image of the synthesized copper particles in Example 2

[0049] Figure 5 Comparison of the coulombic efficiency of the half-cell test composed of modified copper particles, unmodified copper particles, ordinary copper foil and lithium sheet

[0050] Figure 6 This is a comparison chart of the coulombic efficiency of the half-cell test of the modified copper particles coated on PI and the lithium sheet in Example 1

[0051] Figure 7 Comparison of the modified copper particles and the unmodified copper particles in the air (left is the copper particles before modification, right is the copper particles after modification, both concentrations are 2.5g / L)

[0052] Figure 8 The square resistance of the copper film after the composite current collector was sintered in a nitrogen atmosphere and left to stand for different times DETAILED DESCRIPTION

[0053] In order to make the purpose, technical methods, advantages, etc. of the present invention clearer, the following will be further analyzed and explained in conjunction with the accompanying drawings, as well as specific implementation methods and examples of the present invention. It should be clear that the following is only a part of the embodiments and is not intended to limit the scope of implementation of the present invention.

[0054] The specific implementation of the present invention is carried out according to the following steps, specifically: uniform copper nanoparticles are prepared using copper nitrate and hydrazine hydrate as raw materials, the copper nanoparticles are modified with formate, and the modified copper nanoparticles are directly coated on copper foil to form a half-cell with a lithium sheet, and the coulomb efficiency is compared with that of unmodified copper particles and ordinary copper foil to prove its lithium affinity. The modified copper particles are coated on PI to form a composite current collector, the conductivity of the copper film is increased by adding a copper amine ligand and sintering, and the composite current collector and the lithium sheet form a half-cell to test its coulomb efficiency.

[0055] Example 1

[0056] 1) Add 40 mL of 1.25 mol / L copper nitrate solution and 40 mL of 5 mol / L hydrazine hydrate solution to the PVP aqueous solution at the same time. The mass of PVP (polyvinyl pyrrolidone K30) is 5 g, the amount of solvent water is 150 ml, and the temperature of the PVP aqueous solution is selected to be 85°C during the dropwise addition. The dropwise acceleration rate is 8 ml / min. Copper nanoparticles with a particle size of 50-100 nm are obtained, as shown in the attached Figure 2 As shown, the figure shows the SEM image of copper particles coated on copper foil, which are uniform in size and very flat.

[0057] 2) The synthesized copper nanoparticles were modified by dissolving 400 mg of sodium formate and 1 mg of copper formate in 1 ml of water and adding 30 mL of ethylene glycol as a modification solution. 2 g of copper nanoparticles were dissolved in the modification solution and reacted at 160° C. for 1 h, with nitrogen flowing throughout the reaction. After the reaction was completed, the copper nanoparticles were centrifuged at 11,000 r / min to obtain copper particles modified with formate.

[0058] 3) After the modified copper particles are centrifuged, isopropanol is added to wash away impurities, and the particles are centrifuged again at a speed of 11000 r / min for 4 min. After centrifugation, the copper particles are purged with nitrogen to dry most of the solvent, and isopropanol is used as the solvent and dispersed by a homogenizer to prepare a copper slurry with a mass fraction of 34 wt%. The parameters of the homogenizer are 1500 r / min for 8 min.

[0059] 4) The prepared copper paste is directly coated on the copper foil by the scraping method to make the current collector, and then dried in a 40°C oven. The current collector and the lithium sheet are used to form a half-cell and compared with the unmodified copper particles and the ordinary copper foil. Figure 5 As shown, the lithium deposition efficiency of the modified copper particles is greater than that of the unmodified copper particles and greater than that of ordinary copper foil.

[0060] 5) Preparation of copper amine ligand: copper formate and AMP (isobutanolamine) are used for complexation. The molar ratio of copper formate and AMP is 1:2, and the mixture is stirred and reacted at 50° C. for 2 hours to allow the mixture to react fully.

[0061] 6) Add 10 wt% (relative to copper particles) of the prepared copper amine ligand into the copper slurry, and homogenize again, with the same parameters as those in step 3. After homogenization, a new copper slurry is obtained.

[0062] 7) The new copper paste was coated on the PI substrate (thickness 7.5-25 μm) by scraping, the scraper gap was 100 μm, the scraped copper film thickness was about 1 μm, and after sintering at 250°C for 60 min in a nitrogen atmosphere, the volume resistivity of the copper film in the composite current collector was 3 μΩ·cm.

[0063] 8) The sintered composite current collector and lithium sheet were combined into a half-cell for lithium deposition test and compared with ordinary copper foil. The results are as follows Figure 6 shown.

[0064] The reason why the lithium deposition efficiency of unmodified copper particles is higher is that the copper particles provide a larger surface area and more deposition sites. The deposition efficiency of modified copper particles is the highest, proving that the modified copper particles have a certain affinity for lithium. This also proves the feasibility of the present invention.

[0065] The conductivity of the composite current collector prepared by directly coating the copper paste in step 3 on the PI substrate after sintering is insufficient. The conductivity of the copper film can be improved by adding copper amine ligands to the copper paste.

[0066] Example 2

[0067] 1) Add 40 mL of 2.5 mol / L copper nitrate solution and 40 mL of 10 mol / L hydrazine hydrate solution to PVP (polyvinyl pyrrolidone K30) aqueous solution at the same time. The mass of PVP is 5 g, the amount of solvent water is 150 ml, and the temperature of PVP aqueous solution is selected to be 85°C when the addition starts. The drop rate is 4 ml / min. Copper nanoparticles with a particle size of about 200 nm are obtained, as shown in the attached Figure 4 As shown, the figure shows the SEM image of copper particles coated on copper foil, which are uniform in size and very flat.

[0068] 2) The synthesized copper nanoparticles were modified by dissolving 400 mg of sodium formate and 1 mg of copper formate in 1 ml of water and adding 30 mL of ethylene glycol as a modification solution. 2 g of copper nanoparticles were dissolved in the modification solution and reacted at 160° C. for 1 h, with nitrogen flowing throughout the reaction. After the reaction was completed, the copper nanoparticles were centrifuged at 11,000 r / min to obtain copper particles modified with formate.

[0069] 3) Preparation of copper amine ligand: copper formate and AMP (isobutanolamine) are used for complexation. The molar ratio of copper formate and AMP is 1:2, and the mixture is stirred and reacted at 50° C. for 2 hours to allow the mixture to react fully.

[0070] 4) After the modified copper particles are centrifuged, isopropanol is added to wash away impurities, and the particles are centrifuged again at a speed of 11000 r / min for 4 min. After centrifugation, the copper particles are purged with nitrogen to dry most of the solvent, and isopropanol is used as a solvent. The prepared copper amine ligand is added to the copper particles at 10 wt% (relative to the copper particles). The particles are dispersed with a homogenizer and deaerator to prepare a copper slurry with a mass fraction of 34 wt%. The parameters of the homogenizer and deaerator are 1500 r / min, 8 min.

[0071] 5) The new copper paste was coated on the PI substrate (7.5-25 μm) by scraping with a scraper gap of 100 μm. The composite current collector was obtained after sintering at 250° C. for 60 min in a nitrogen atmosphere.

[0072] The main difference between Example 2 and Example 1 is that the copper particle synthesis process is changed to synthesize copper particles of different sizes.

[0073] In other embodiments, methods of changing the process include but are not limited to changing the raw material concentration, changing the type of copper salt, changing the drop rate and the reaction temperature, etc.

[0074] Example 3

[0075] 1) 40 mL of 1.25 mol / L copper nitrate solution and 40 mL of 5 mol / L hydrazine hydrate solution were simultaneously added dropwise to the PVP aqueous solution. The mass of PVP was 5 g and the amount of solvent water was 150 ml. When the addition began, the temperature of the PVP aqueous solution was selected to be 85°C. The dropwise acceleration rate was 8 ml / min. Copper nanoparticles with a particle size of about 50 nm were obtained. Figure 4 As shown, the figure shows the SEM image of copper particles coated on copper foil, which are uniform in size and very flat.

[0076] 2) The synthesized copper nanoparticles were modified by dissolving 400 mg of sodium formate and 1 mg of copper formate in 1 ml of water and adding 36 mL of DMF as a modification solution. 2 g of copper nanoparticles were dissolved in the modification solution and reacted at 120° C. for 1 h, with nitrogen flowing throughout the reaction. After the reaction was completed, the copper nanoparticles were centrifuged at 11,000 r / min to obtain copper particles modified with formate.

[0077] 3) Preparation of copper amine ligand: copper formate and isopropanolamine are used for complexation. The molar ratio of copper formate and isopropanolamine is 1:2, and the mixture is stirred and reacted at 50° C. for 2 hours to allow the mixture to react fully.

[0078] 4) After the modified copper particles are centrifuged, isopropanol is added to wash away impurities, and the particles are centrifuged again at a speed of 11000 r / min for 4 min. After centrifugation, the copper particles are purged with nitrogen to dry most of the solvent, and isopropanol is used as a solvent. The prepared copper amine ligand is added to the copper particles at 10 wt% (relative to the copper particles). The particles are dispersed with a homogenizer and deaerator to prepare a copper slurry with a mass fraction of 34 wt%. The parameters of the homogenizer and deaerator are 1500 r / min, 8 min.

[0079] 5) The new copper paste was coated on the PI substrate by a scraper coating method with a scraper gap of 100 μm. The composite current collector was obtained after sintering at 250° C. for 60 min in a nitrogen atmosphere.

[0080] The main difference between Example 3 and Example 1 is that the solvent in the modification process is changed, and the modification solution solvent includes but is not limited to ethylene glycol and DMF. In addition, the type of amine is changed in the preparation of the copper amine ligand, and other amines that can form copper amine ligands (such as 3-dimethylamino-1,2-propylene glycol, pentylamine, etc.) are also included.

[0081] It should be noted that the substrate material mentioned in the embodiment includes but is not limited to PI (polyimide) material, and other flexible and high temperature resistant substrate materials may also be used.

[0082] Example 4

[0083] 1) Add 40 mL of 1.25 mol / L copper nitrate solution and 40 mL of 5 mol / L hydrazine hydrate solution to the PVP aqueous solution at the same time. The mass of PVP (polyvinyl pyrrolidone K30) is 5 g, the amount of solvent water is 150 ml, and the temperature of the PVP aqueous solution is selected to be 85°C during the dropwise addition. The dropwise acceleration rate is 8 ml / min. Copper nanoparticles with a particle size of 50-100 nm are obtained, as shown in the attached Figure 2 As shown, the figure shows the SEM image of copper particles coated on copper foil, which are uniform in size and very flat.

[0084] 2) The synthesized copper nanoparticles were modified by dissolving 400 mg of sodium formate and 1 mg of copper formate in 1 ml of water and adding 30 mL of ethylene glycol as a modification solution. 2 g of copper nanoparticles were dissolved in the modification solution and reacted at 160° C. for 1 h, with nitrogen flowing throughout the reaction. After the reaction was completed, the copper nanoparticles were centrifuged at 11,000 r / min to obtain copper particles modified with formate.

[0085] 3) After the modified copper particles are centrifuged, isopropanol is added to wash away impurities, and the particles are centrifuged again at a speed of 11000 r / min for 4 min. After centrifugation, the copper particles are purged with nitrogen to dry most of the solvent, and isopropanol is used as the solvent and dispersed by a homogenizer to prepare a copper slurry with a mass fraction of 34 wt%. The parameters of the homogenizer are 1500 r / min for 8 min.

[0086] 4) The prepared copper paste is directly coated on the copper foil by the scraping method to make the current collector, and then dried in a 40°C oven. The current collector and the lithium sheet are used to form a half-cell and compared with the unmodified copper particles and the ordinary copper foil. Figure 5 As shown, the lithium deposition efficiency of the modified copper particles is greater than that of the unmodified copper particles and greater than that of ordinary copper foil.

[0087] 5) Preparation of copper amine ligand: copper formate and AMP (isobutanolamine) are used for complexation. The molar ratio of copper formate and AMP is 1:2, and the mixture is stirred and reacted at 50° C. for 2 hours to allow the mixture to react fully.

[0088] 6) Add 10 wt% (relative to copper particles) of the prepared copper amine ligand into the copper slurry, and homogenize again, with the same parameters as those in step 3. After homogenization, a new copper slurry is obtained.

[0089] 7) The new copper paste was coated on a PPS substrate (thickness 7.5-25 μm) by scraping, with a scraper gap of 100 μm and a copper film thickness of about 1 μm. The composite current collector was obtained after sintering at 250° C. for 60 min in a nitrogen atmosphere.

[0090] Example 5

[0091] 1) Add 40 mL of 1.25 mol / L copper nitrate solution and 40 mL of 5 mol / L hydrazine hydrate solution to the PVP aqueous solution at the same time. The mass of PVP (polyvinyl pyrrolidone K30) is 5 g, the amount of solvent water is 150 ml, and the temperature of the PVP aqueous solution is selected to be 85°C during the dropwise addition. The dropwise acceleration rate is 8 ml / min. Copper nanoparticles with a particle size of 50-100 nm are obtained, as shown in the attached Figure 2 As shown, the figure shows the SEM image of copper particles coated on copper foil, which are uniform in size and very flat.

[0092] 2) The synthesized copper nanoparticles were modified by dissolving 400 mg of sodium formate and 1 mg of copper formate in 1 ml of water and adding 30 mL of ethylene glycol as a modification solution. 2 g of copper nanoparticles were dissolved in the modification solution and reacted at 160° C. for 1 h, with nitrogen flowing throughout the reaction. After the reaction was completed, the copper nanoparticles were centrifuged at 11,000 r / min to obtain copper particles modified with formate.

[0093] 3) After the modified copper particles are centrifuged, isopropanol is added to wash away impurities, and the particles are centrifuged again at a speed of 11000 r / min for 4 min. After centrifugation, the copper particles are purged with nitrogen to dry most of the solvent, and isopropanol is used as the solvent and dispersed by a homogenizer to prepare a copper slurry with a mass fraction of 34 wt%. The parameters of the homogenizer are 1500 r / min for 8 min.

[0094] 4) The prepared copper paste is directly coated on the copper foil by the scraping method to make the current collector, and then dried in a 40°C oven. The current collector and the lithium sheet are used to form a half-cell and compared with the unmodified copper particles and the ordinary copper foil. Figure 5 As shown, the lithium deposition efficiency of the modified copper particles is greater than that of the unmodified copper particles and greater than that of ordinary copper foil.

[0095] 5) Preparation of copper amine ligand: copper formate and AMP (isobutanolamine) are used for complexation. The molar ratio of copper formate and AMP is 1:2, and the mixture is stirred and reacted at 50° C. for 2 hours to allow the mixture to react fully.

[0096] 6) Add 10 wt% (relative to copper particles) of the prepared copper amine ligand into the copper slurry, and homogenize again, with the same parameters as those in step 3. After homogenization, a new copper slurry is obtained.

[0097] 7) Apply the new copper paste on the polytetrafluoroethylene substrate (thickness 7.5-25 μm) by scraping, the scraper gap is 100 μm, the scraped copper film thickness is about 1 μm, and the composite current collector is obtained after sintering at 250°C for 60 minutes in a nitrogen atmosphere.

[0098] from Figure 8It can be seen that after sintering, the copper nanoparticles of the composite current collector are connected, making it conductive, which is used to meet the conductivity requirements of the current collector in the battery. However, the unmodified copper nanoparticles do not have conductivity after sintering.

[0099] pass Figure 6 From the comparison of coulombic efficiency, it can be found that the efficiency of the composite current collector prepared in Example 1 of the present invention is maintained at about 98% after more than 70 cycles in the lithium deposition test, while the efficiency of ordinary copper foil is significantly attenuated after more than 20 cycles.

[0100] Comparison of copper particle dispersion before and after modification ( Figure 7 ) It can be seen that the color of the copper particles modified with formate remains red after standing for fifteen days. The color of the unmodified copper particles turns yellow after standing in the air. This shows that the oxidation resistance of copper particles can be improved by formate modification. It also proves the advantages and application prospects of the composite current collector of the present invention.

Claims

1. A lightweight, lithium-philic composite current collector, characterized in that: It comprises a plastic base layer and a wet chemical copper particle layer attached to the plastic surface, wherein the plastic base layer has a thickness ranging from 4 to 12 μm, the wet chemical copper nanoparticle layer has a thickness ranging from 500 nm to 1.5 μm, and the surface of the wet chemical copper nanoparticles is treated with formate and sintered at 200 to 270° C. for 20 to 80 min; The method for preparing the lightweight, lithium-philic composite current collector comprises the following steps: 1) Synthesis of copper nanoparticles by wet chemical method; 2) dispersing copper nanoparticles in a modification solution and modifying the surface with formate by heating; 3) coating the modified copper particles on a plastic substrate material to obtain a composite current collector; 4) Sinter the composite current collector at 200-270° C. for 10-60 min.

2. A lightweight, lithium-philic composite current collector according to claim 1, characterized in that: The plastic base layer is at least one of PPS, PAR, PI, PEEK, POB, EP, and PF.

3. A method for preparing a lightweight, lithium-philic composite current collector according to claim 1 or 2, comprising the following steps: 1) Synthesis of copper nanoparticles by wet chemical method; 2) dispersing copper nanoparticles in a modification solution and modifying the surface with formate by heating; 3) coating the modified copper particles on a plastic substrate material to obtain a composite current collector; 4) Sinter the composite current collector at 200-270° C. for 10-60 min.

4. A method for preparing a lightweight, lithium-philic composite current collector according to claim 3, characterized in that: In step 1), copper nitrate and hydrazine hydrate solution are simultaneously added dropwise to a polyvinyl pyrrolidone aqueous solution to react and obtain a copper nanoparticle dispersion.

5. A method for preparing a lightweight, lithium-philic composite current collector as claimed in claim 4, characterized in that: Step 1) The copper nitrate concentration is 0.5-3 mol / L, the hydrazine hydrate concentration is 3-7 mol / L, and the PVP mass concentration is 0.01-0.10 g / mL; the volume ratio of copper nitrate solution: hydrazine hydrate solution: PVP aqueous solution is 30-50:30-50:120-180.

6. A method for preparing a lightweight, lithium-philic composite current collector according to claim 4, characterized in that: The copper nitrate and hydrazine hydrate are added dropwise simultaneously, with a dropping rate of 5 to 10 mL / min and a temperature of 75 to 95° C. during the dropping.

7. A method for preparing a lightweight, lithium-philic composite current collector according to claim 3, characterized in that: Step 2) The modification solution is obtained by dissolving sodium formate and copper formate in ethylene glycol, wherein the concentration of sodium formate is 0.05-0.5 mol / L, and the concentration of copper formate is 0.00005-0.0005 mol / L.

8. A method for preparing a lightweight, lithium-philic composite current collector according to claim 7, characterized in that: The mass concentration of the copper particles in the modification solution is 0.01-0.5 g / mL.

9. A method for preparing a lightweight, lithium-philic composite current collector according to claim 7, characterized in that: During the modification process, nitrogen or inert gas is passed and the temperature is maintained at 120-180° C. for 0.5-2 h.

10. The method for preparing a lightweight, lithium-philic composite current collector according to claim 3, characterized in that: Step 3) The modified copper particles are first configured into copper paste and then coated, wherein the solvent used in the copper paste is isopropanol, and the mass fraction of the copper particles is 30-40wt%.

Citation Information

Patent Citations

  • Novel current collector for battery and preparation method thereof

    CN112615010A

  • Negative electrode copper foil for soft package lithium battery and preparation method of negative electrode copper foil

    CN114161787A

  • Surface processing method for copper-containing material

    CN107460464A

  • Copper nano-particles, method of preparing the same, and method of forming copper coating film using the same

    US20070180954A1